Vloga gozdov pri ohranjanju biotske pestrosti na krajinski ravni - nekatera izhodišča za krajinskoekološko tipizacijo - Anko, Boštjan (Zbornik gozdarstva in lesarstva, 2000)
The concept of biodiversity is not new to the natural sciences. In forestry, too, it has been present for such a long time that it sometimes requires redefining. Clear definitions are prerequisite for an efficient integration ofthe idea of biodiversity into contemporary forestry. As in the case of cultural landscapes the majority of biodiversity is a dynamic anthropogenic category - from gene to ecosystem and higher levels. Until now, forestry has primarily paid attention to the species, partly gene biodiversity. It neglected somehow higher biodiversity levels, recently being discovered by theidea of landscape forestry. This can be proven by a series of internationaldocuments - from the Helsinki to Lisbon resolutions. Nevertheless, the fact has to be accepted that all biodiversity levels and conservation thereof are inseparably connected. Typifying forest landscapes can be considered as one of the means of forest related biodiversity conservation. Contrary to previous cases such typifying is not based solely onthe physical presence of the forest (area, distribution patterns). It is based primarily on forest properties that are biodiversity friendly and renderpossible communications of organisms - from gene level to migratory movements. The new paradigm of sustainable forest management for biodiversity will require that forestry actively take part in complying with many obligations related to international documents.
Keywords: biodiversity; biodiverziteta; biotska raznovrstnost; forestry; gozdarstvo; krajinska ekologija